Development of Prediction Models for Motorcycle Crashes at Signalized Intersections on Urban Roads in Malaysia - Sulistio, Harnen; Radin Sohadi, Radin Umar; Wong, Shaw Voon; Wan Ibrahim, Wan Hashim (Bureau of Transportation Statistics, 2004)
Because more than half the motor vehicles in Malaysia are motorcycles, safety of this from of transportation is an important issue. As part of a motorcycle safety program, Malaysia became the first country to provide exclusive motorcycle lanes in the hopes of reducing motorcycle crashes along trunk roads. However, little work has been done to address intersection crashed involving motorcycles. This paper provides models for predicting motorcycle crashes at signalized intersections on urban roads in Malaysia. A generalized linear modeling technique with quasilikelihood approach was adopted to develop the models. Traffic entering the intersection, approach speed, lane width, number of lanes, shoulder width, and land use at the approach of the intersections were found to be significant in describing motorcycle crashes. These findings should enable engineers to draw up appropriate intersection treatment criteria specifically designed for motorcycle lane facilities in Malaysia and elsewhere.